Performance comparison of capacitive power transfer between matching resonant circuit Ï€1a and Ï€1b at 13.56 MHz operating frequency - Muslimah Meor; Yusmarnita Yusop; Shakir Saat; Khairul Kamarudin Hasan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper proposes current technique for wireless power transfer (WPT), which is capacitive power transfer (CPT). To date, inductive power transfer (IPT) remains the most popular technique for this technology. However, CPT has several benefits which make the development of this technique is growing up faster in industry and able to compete the IPT technology. A low number of components usage, simple topology, enhanced EMI performance, robustness to surrounding metallic elements are the benefits of CPT. In this work, the system is designed using class E power amplifier with the presence of impedance matching circuit. It assists the system to attain maximum power transfer. Two types of impedance matching are selected and compared in this work in order to understand the advantage and disadvantage of each in the framework of CPT system. MATLAB/Simulink software is used in this work to design and simulate the CPT system. This proposed system ables to generate 0.83W output power through a combined interface capacitance of 0.024nF at an operating frequency of 13.56 MHz, with 99.2% efficiency for both matching resonant circuits Ï€1a and Ï€1b. In the case for biomedical implantable device application, Ï€1b is the superior matching resonant circuit since it requires smaller capacitance value and smaller size of receiver unit.